(untitled) (The Peerian Journal, 2022)
The issue of restoring children’s ability to work faster is one of the most complex issues in the study of students’ agenda and load of learning . Influenced by favorable conditions of the external environment, the organism of children and adolescents grows and grows up. When the agenda is properly organized, the child is not tired, stereotypes are formed in the nervous system, and children become disciplined and disciplined. When the order of the day is not followed, the child becomes fully resting, his sleep, his appetite deteriorates, his temper deteriorates, and his work abilities decrease. An agenda that can ensure a wise distribution of work and leisure time during the day is of great importance in maintaining students’ long, time-spanning ability and nervous system arousal at a high level.